2021
DOI: 10.1172/jci.insight.149033
|View full text |Cite
|
Sign up to set email alerts
|

Gut germinal center regeneration and enhanced antiviral immunity by mesenchymal stem/stromal cells in SIV infection

Abstract: While antiretroviral therapy suppresses HIV replication, it does not eliminate viral reservoirs or restore damaged lymphoid tissue, posing obstacles to HIV eradication. Using the simian immunodeficiency virus (SIV) model of AIDS, we investigated the effect of mesenchymal stem/stromal cell (MSC) infusions on gut mucosal recovery, anti-viral immunity, viral suppression and determined associated molecular/metabolic signatures. MSC administration to SIV-infected macaques resulted in viral reduction and heightened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…RNAseq analysis was performed in Illumina HiSeq 4,000 system as previously described ( Weber et al, 2021 ). In brief, total RNA was extracted using the (QIAGEN RNeasy RNA isolation kit) from ileum tissues and treated with DNase (QIAGEN RNase-Free DNase Kit).…”
Section: Methodsmentioning
confidence: 99%
“…RNAseq analysis was performed in Illumina HiSeq 4,000 system as previously described ( Weber et al, 2021 ). In brief, total RNA was extracted using the (QIAGEN RNeasy RNA isolation kit) from ileum tissues and treated with DNase (QIAGEN RNase-Free DNase Kit).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most interesting studies focused on the use of MSCs to increase antiviral immune activity and minimize the amount of virus. It has been shown that the administration of MSCs, even in the absence of antiviral drugs, can enhance the host’s antiviral response due to the restoration of lymphoid follicles and mucosal immunity, all of which become the target of the virus at an early stage [ 194 ]. The results of scientific and clinical studies provide an appropriate scientific basis for the future use of MSCs in the treatment of HIV and other infectious diseases.…”
Section: Viral Infectious Diseasesmentioning
confidence: 99%
“…However, MSCs can promote the proliferation of virus-specific immune cells and their antiviral exertion [ 20 , 21 ]. For example, using the SIV model of AIDS, some researchers have recently found that MSCs can restore antiviral immunity by reconstituting damaged lymphoid follicles, as evidenced by robust regeneration of germinal centers, as well as restoration of follicular B cells and Tfh cells leading to increased levels of anti-SIV antibodies and SIV-specific CD8 + T cells, resulting in viral reduction [ 539 ]. Similarly, a phase II randomized, double-blinded, multicenter, placebo- controlled, dose-determination trial in 72 immune nonresponder (INR) patients with chronic HIV-1 infection showed that treatment with huMSCs was safe, with a significant increase in CD4 + T cells counts in HIV-infected patients after 48 weeks of treatment, although a larger cohort studies are needed to further confirm the immune reconstitution efficacy of MSCs [ 540 ].…”
Section: Mscs For Immunocompromised Liver Diseasesmentioning
confidence: 99%